Princípio Biocêntrico: A contribuição do Pensamento de Rolando Toro para o campo da Educação. - Guedes, Ricardo Ferreira (2012)
This research bibliographic aims to determine whether the proposal prepared by the Principle Biocentric, Chilean Rolando Toro breaks new conceptual methodological, to the field of Education. The relationship between the biocentric paradigms Principle as an object of research does highlight some contributions to education among which we highlight: affection as a factor that promotes learning, emotional intelligence as a vital aspect to contemporary education, body language as knowledge based a sensitive logic, the historicity of the body and ethical conduct. We take the theoretical creator of this theme Rolando Toro, Elisa Gonsalves, Fritjof Capra, David Bohm, and Nobert Elias, Humberto Maturana and Francisco Varela and others. The theoretical construction on the sensitive, intuitive and what is felt, lived and experienced in the here and now, through stimulation pro-life, provides elements for building a basic epistemological arguments that articulates the understanding of the human body in its relationship with the environment , culture and society in which they live, as well as the phenomenon of cognition as a text body, advocating a design for human development in multiple dimensions: cognitive, social, cultural, experiential, emotional, spiritual, ethical and affective.